Multi-hit model on CR-39, DAM-ADC and LR-115 SSNTDs: Statistical and comparative study. (October 2017) - Awad, E.M.
Abstract: Fourteen versions of different approximations on the basis of the many-hit model (MHM) of etching that proposed by Ditlov (Ditlov, 2005) have been used to calculate the bulk etch rate for three different detectors. The reliability of the model in describing the etching processes and to determine possible physical based parameters was determined. Minimizing the least square deviation between experimental and calculated bulk etch rate enable to calculate the registration parameters of the calculated bulk etch rate of CR-39, DAM-ADC and LR-115 SSNTDs that were etched in different etching conditions. The non-linear fit between experimental bulks etch rate and the different formulae were iteratively obtained. Multi-hit model shows its ability to assign specific adjusting parameters for each detector under investigation. Parameters that can be used to distinguish between detectors such as number of hits, ν the normalized value, B activation energy of etching, ε characteristic concentration, C o and sensitive microscopic volume, SMV diameter were determined. Reasonable number of adjusting parameters for each detector were deduced and statistically compared. Each detector now has, for the first time, its own set of MHM adjusting parameters for standard etching conditions ( T, C ). Highlights: Bulk etch rate calculated by ν-hit model to three SSNTDs. Fourteen formula based on ν-hit model have been used to estimate V B . Detector registration parameters are determined. Parameters are number of hits, ν activation energy, ε characteristic concentration, Co, diameter of sensitive microscopic volume. Detector registration parameters are statistically compared. Each detector assigned to its own registration parameters.